2017
DOI: 10.1159/000484126
|View full text |Cite
|
Sign up to set email alerts
|

Total Outflow Facility in Live C57BL/6 Mice of Different Age

Abstract: Purpose: To characterize total outflow facility across the live adult mouse lifespan as a reference for mouse glaucoma studies and the common C57BL/6 background strain. Methods: Microperfusion was performed by single-needle cannulation and feedback-controlled coupling of pressure and flow to maintain a constant pressure in the anterior chambers of live C57BL/6NCrl mice aged 3-4 months (n = 17), 6-9 months (n = 10), and 23-27 months (n = 12). This mouse age range represented an equivalent human age range of you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…This would result in a shunting of flow from the unconventional to the conventional outflow tract [65], which in turn would require an increase in facility to maintain a desired IOP. Such an increase is consistent with two previous studies that examined outflow facility in aging mice; each reported an increase, or a trend towards an increase, in outflow facility in 3 of 4 strains studied, including C57 mice [66,67].…”
Section: Discussionsupporting
confidence: 92%
“…This would result in a shunting of flow from the unconventional to the conventional outflow tract [65], which in turn would require an increase in facility to maintain a desired IOP. Such an increase is consistent with two previous studies that examined outflow facility in aging mice; each reported an increase, or a trend towards an increase, in outflow facility in 3 of 4 strains studied, including C57 mice [66,67].…”
Section: Discussionsupporting
confidence: 92%
“…Gabelt et al, 2003), which in turn would require an increase in facility to maintain a desired IOP. Such an increase is consistent with two previous studies that examined outflow facility in aging mice; each reported an increase, or trend towards an increase, in outflow facility in three of four strains studied, including C57 mice (Millar et al, 2015;Yelenskiy et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the results of the present study suggested that brimonidine also may enhanced outflow facility. Although there is a concern that the outflow pathway after TM may be different from normal due to the slightly higher intraocular pressure used in our two-level constant pressure method, there have been several previous studies using similar methods [54][55][56] and studies examining the correlation between IOP values and outflow facility measurements have shown that linearity is maintained within the range of IOP values used in this study 57 . So far, several methods have been reported for the measurement of outflow facility in the past, but there are several factors that can affect the results of each method 58,59 and no uniform method has been established.…”
Section: Discussionmentioning
confidence: 87%